Rare earth phosphors based on spherical infinite coordination polymers. (5th November 2018) - Arroyos, Guilherme; Frem, Regina Célia Galvão
Abstract : New spherical lanthanide infinite coordination polymer (ICP)-based phosphors were obtained and show great potential for light-emitting applications. Abstract : A novel luminescent infinite coordination polymer (Tb-M ), constructed by the interaction between Tb 3+ ions and 3, 5-pyrazoledicarboxylate and malonate linkers, was prepared by water microwave-assisted synthesis. The material self-assembles into amorphous microspherical particles. Under UV excitation, a very intense green luminescence is observed by the naked eye at room temperature forTb-M . A Gd 3+ analogue compound (Gd-M ) was also synthesized. Successful attempts at codopingTb-M andGd-M samples with Eu 3+ and Dy 3+ ions were carried out and different emission colors were obtained, including white-light emission.